Metabolic and contractile protein expression in developing rat diaphragm muscle - Kelly, AM (J Neurosci, 1991)
Progressive changes in myosin isozyme expression and in energy- generating enzyme activities were followed in the diaphragm and, for comparison, in axial and appendicular muscles of rats from 18 d gestation to maturity. Native myosins were characterized by pyrophosphate gel electrophoresis. Myosin heavy-chain (MHC) isozymes were measured with ELISA using monoclonal antibodies and were localized by immunocytochemistry. RNA transcripts for the MHCs were demonstrated on Northern blots and by RNase protection assays. Quantitative activities of malate dehydrogenase (MDH), beta-hydroxyacyl CoA dehydrogenase (beta OAC), 1-phosphofructokinase (PFK), lactate dehydrogenase (LDH), creatine kinase (CK), and adenylokinase (AK) were measured in muscle homogenates and in individual fibers by fluorometric pyridine nucleotide-dependent assays. Compared to limb muscles, expression of neonatal myosin in the diaphragm is precocious. Neonatal MHC mRNA is prominent in the diaphragm at 19 d gestation, and neonatal myosin is the major MHC isoform present at birth. Slow and fast IIa MHCs are also present at birth. Transcripts for IIa MHC are detectable in the diaphragm at 21 d gestation and are upregulated at birth. Comparable signal for IIa MHC mRNA is not found in the gastrocnemius until 10 d postpartum. Adult fast IIb MHC mRNA was detected only as a faint signal at 30–40 d in the diaphragm and then disappeared. Results indicate that a separate phenotype, the IIx type, matures late in diaphragmatic development. The activities of enzymes representing all of the major energy pathways are higher in the fetal diaphragm than in the fetal hindlimb muscles. For example, beta OAC had sixfold higher activity in the diaphragm than in the extensor digitorum longus (EDL) muscle at birth, activity in the diaphragm than in the extensor digitorum longus (EDL) muscle at birth.